A mixed-integer linear programming model for optimal synthesis of polygeneration systems with material and energy storage for cyclic loads - Aviso, Kathleen B. (Animo Repository, 2015)
© 2015 by Taylor & Francis Group, LLC. Polygeneration plants offer the prospect of efficient utilization of fuel inputs, as well as minimal generation of carbon emissions, relative to separate generation of individual streams of electricity, heat, cooling, and other products (Chicco and Mancarella, 2009; Serra et al., 2009). They are also particularly well-suited to applications requiring stand-alone facilities to provide energy self-sufficiency, for instance, in the case of residential buildings, hospitals and hotels, and so on (Lozano et al., 2009b, 2011). To some extent, the topology of polygeneration plants can be designed to allow some degree of operational flexibility; however, it has also been noted that the interdependence among process units may also lead to vulnerability to failure, as process unit inoperability may cascade through a process network via stream linkages (Tan et al., 2012; Kasivisvanathan et al., 2013).